Ketogenic diet prevents chronic sleep deprivation-induced Alzheimer’s disease by inhibiting iron dyshomeostasis and promoting repair via Sirt1/Nrf2 pathway - Yang, Yueqi; Wang, Xueyan; Xiao, Aiai; Han, Jun; Wang, Zhengping; Wen, Min (Frontiers in Aging Neuroscience, 2022)
Sleep deprivation (SD) is one of the main risk factors for Alzheimer’s disease (AD), but the underlying mechanism is still unclear. Ketogenic diet (KD) has been shown widely neuroprotective effects but less known about its effect on SD-induced AD. In the present study, a continuous 21 days SD mouse model with or without KD was established. The changes of cognitive function, pathological hallmarks of AD, ferroptosis, and intracellular signal pathways in mice were detected by Morris water maze, ThS staining, diaminobenzidine (DAB)-enhanced Perls’ stain, antioxidant assay, immuno-histochemistry, and western blot. The results showed that KD can prevent the cognitive deficiency, amyloid deposition and hyperphosphorylated tau induced by chronic SD. Analysis of ferroptosis revealed that KD can inhibit iron dyshomeostasis by down-regulating the expression of TfR1 and DMT1 and up-regulating the expression of FTH1, FPN1. Meanwhile, KD alleviated oxidative stress with elevated xCT/GPX4 axis, FSP1 and reduced MDA. In addition, KD could promote neuronal repair by enhancing BDNF and DCX. Further studies demonstrated that KD activated Sirt1/Nrf2 signaling pathway in the hippocampus in SD-exposed mice. Our finding firstly suggested that KD could prevent chronic SD-induced AD by inhibiting ferroptosis and improving the neuronal repair ability via Sirt1/Nrf2 signaling pathway.